Comparative effects of desflurane and sevoflurane on recovery time in patients undergoing modified radical mastectomy: a cross-sectional study - Muhammad Rodli; Suryanto Suryanto; Reko Priyonggo; Sindu Sintara; Annes Rindy Permana; Widigdo Rekso Negoro (Intelektual Pustaka Media Utama, 2026)
Fast and predictable recovery is essential in breast cancer surgery, yet comparative evidence on inhalation anesthetics within Indonesian clinical settings remains limited. This study compared the effectiveness of desflurane and sevoflurane on early recovery time after modified radical mastectomy. A cross-sectional design was applied to 76 ASA I-II female patients who received standardized induction, maintenance, and Aldrete-based recovery assessment. Recovery was categorized as fast (≤10 minutes) or delayed (>10 minutes). Statistical analysis used Chi-square testing, supported by effect size and risk ratio estimation. Desflurane demonstrated significantly faster recovery than sevoflurane (97.4% vs 78.9%, p = 0.014). The association showed a moderate effect size (Cramér’s V = 0.30), and patients receiving sevoflurane were substantially more likely to experience delayed recovery (RR = 8.3). These results align with recent studies highlighting desflurane’s lower blood-gas solubility and faster elimination profile. The homogeneous sample and standardized anesthetic protocol strengthen internal validity. However, the non-randomized design, purposive sampling, and absence of documented adverse events limit generalizability. Desflurane may offer practical benefits in improving post-anesthesia care unit (PACU) efficiency and surgical throughput in high-volume settings. Further multicenter randomized studies are recommended to confirm these findings and explore broader clinical implications.